The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/pace.13416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defibrillation threshold testing on effectiveness of the subcutaneous implantable cardioverter defibrillator

Abstract: A strategy that omits DFT testing at implant did not appear to compromise the effectiveness of the SICD. These data suggest that routine DFT testing at SICD implant might not be necessary. Randomized trials are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Recent observations have reported that DT is declining also in S‐ICD owing to physician and patients' preference, despite being a Class 1 recommendation, but only scarce data on device functioning at follow‐up have been reported to date 7,10,13,16,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations have reported that DT is declining also in S‐ICD owing to physician and patients' preference, despite being a Class 1 recommendation, but only scarce data on device functioning at follow‐up have been reported to date 7,10,13,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Eventually, clinical arrhythmias are different from induced ones, and frequently arise in conditions (ischemia, acidosis, heart failure, supraventricular arrhythmias) that can impact on defibrillation threshold or promote re‐initiation after a successful shock. Despite all these objections, data regarding outcomes of S‐ICD patients not undergoing DT are scarce 17 …”
Section: Discussionmentioning
confidence: 99%
“…One analysis showed no difference in mortality between the S-ICD and transvenous ICD when no DFT was performed during implant [25]. A retrospective comparison between S-ICD with and without DFT during implant showed no effect on first shock efficacy of the device [26] and a third analysis reported successful defibrillation of all spontaneous ventricular arrhythmias (n = 6) after no DFT was performed during implant [27]. On the other hand, one study reported sustained noise oversensing during induced VF in 4% of S-ICD patients, which resulted in delay of therapy, [28] although this could be the result of oversensing of myopotentials by the diaphragmatic muscles caused by the induction of VF [29].…”
Section: Omission Of Dft In S-icd Implantsmentioning
confidence: 99%
“…An episode is only terminated when VT of VF is terminated, either spontaneously or by shock delivery. Based on the first shock efficacy in EFFORTLESS and IDE the norm for shock efficacy of the S-ICD for the first shock was set at 90% (12,13,14). We assume that the shock efficacy remains unchanged for subsequent shocks.…”
Section: Non-inferiority Marginmentioning
confidence: 99%
“…This movement has already started prior to the outcome of the SIMPLE and NORDIC trials. Although DFT in S-ICD is linked with mostly similar risks of complications and logistic burden as transvenous devices there are currently only a few studies available on the efficacy of DFT in S-ICD (9)(10)(11)(12). Nevertheless, DFT is already omitted for a substantial number of patients receiving S-ICD, as was demonstrated by the Subcutaneous ICD Post-Market Approval Study (PAS).…”
Section: Introductionmentioning
confidence: 99%